Humeral Avulsion of the Lateral Collateral Ligament of the Elbow Concomitant with the Medial Epicondyle Fracture of a Child with General Joint Laxity - Toru Morimoto; Masashi Izumi; Hiroaki Ueba; Masahiko Ikeuchi (Case Reports in Orthopedics)
Medial epicondyle fracture is a common elbow injury for children, and it was reported that 30-50% of this fracture was associated with elbow dislocation. However, dysfunction of the lateral collateral ligament (LCL) complex accompanied with the medial epicondyle fracture has rarely been reported. In this report, a 13-year-old girl who had a humeral avulsion of the LCL concomitant with a displaced medial epicondyle fracture was presented. Since her general joint laxity had been recognized from past medical history and the humeral avulsion of the LCL was clearly confirmed by ultrasonography, simultaneous surgical repair for the LCL avulsion and medial epicondyle fracture was conducted and satisfactory outcome was achieved. Although general joint laxity does not tend to receive attention in trauma as much as chronic conditions, it should be borne in mind to prevent overlooking important soft tissue damage coexisting with apparent fractures.